Comparison of Team Sports and Individual Sports on Health Status and Emotional Intelligence of Children Aged 13-16 Years - Gandang Eka Prayoga; Anung Priambodo; Noortje Anita Kumaat (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
This study aims to determine the comparison of team sports and individual sports on the health status and emotional intelligence of children aged 13-16 years. In this study, the research method used is a quantitative approach with experimental research methods. The data analysis technique used MANOVA. The data collection process was carried out using a questionnaire instrument, namely the KIDSCREEN-27 questionnaire to measure health status and the Trait Emotional Intelligence Questionnaire-Adolescent Short Form was used to measure emotional intelligence. Then the data is processed using the SPSS version 22.0 application. The results showed: (1) There was a significant difference between team sports and individual sports on the health status of children aged 13-16 years with a significant value of 0.007 < 0.05; (2) There is no difference in the effect of team sports and individual sports on the emotional intelligence of children aged 13-16 years with a significant value of 0.918 > 0.05.